T-cell receptors identified by a personalized antigen-agnostic screening approach target shared neoantigen KRAS Q61H - Lennerz, Volker; Doppler, Christoph; Fatho, Martina; Dröge, Anja; Schaper, Sigrid; Gennermann, Kristin; Genzel, Nadine; Plassmann, Stephanie; Weismann, David; Lukowski, Samuel W.; Bents, Dominik; Beushausen, Christina; et al. (Frontiers in Immunology, 2025)
Adoptive cell therapy (ACT) with TCR-engineered T-cells represents a promising alternative to TIL- or CAR-T therapies for patients with advanced solid cancers. Currently, selection of therapeutic TCRs critically depends on knowing the target antigens, a condition excluding most patients from treatment. Direct antigen-agnostic identification of tumor-specific T-cell clonotypes and TCR-T manufacturing using their TCRs can advance ACT for patients with aggressive solid cancers. We present a method to identify tumor-specific clonotypes from surgical specimens by comparing TCRβ-chain repertoires of TILs and adjacent tissue-resident lymphocytes. In six out of seven NSCLC-patients analyzed, our selection of tumor-specific clonotypes based on TIL-abundance and high tumor-to-nontumor frequency ratios was confirmed by gene expression signatures determined by scRNA-Seq. In three patients, we demonstrated that predicted tumor-specific clonotypes reacted against autologous tumors. For one of these patients, we engineered TCR-T cells with four candidate tumor-specific TCRs that showed reactivity against the patient’s tumor and HLA-matched NSCLC cell lines. The TCR-T cells were then used to screen for candidate neoantigens and aberrantly expressed antigens. Three TCRs recognized recurrent driver-mutation KRAS Q61H-peptide ILDTAGHEEY presented by HLA-A*01:01. The TCRs were also dominant in a tumor relapse, one was found in cell free DNA. The finding of homologous TCRs in independent KRAS Q61H-positive cancers suggests a therapeutic opportunity for HLA-matched patients with KRAS Q61H-expressing tumors.